(untitled) (Research, Society and Development, 2021)
The present work aims to verify the perception of members of riverside communities in the Sustainable Reserve of Rio Negro, Amazonas, on changes in landscape dynamics generated by extreme hydroclimatic events. Workshops of mind maps will be held in four communities of the reserve, which are: Tiririca, Santo Antonio and Marajá, in the municipality of Novo Airão and Terra Preta in the municipality of Iranduba. Fivety community members participated, divided into focus groups of men and women. Both groups were oriented to draw up a mental map in which ilustrate: A long period of drought and a long period of avenue in Rio Negro. It was observed that it differentiates in the perception between the genres about these extreme events. Finally, each group displayed in detail the maps made to all participants and organizers of the workshop. Among the answers, two groups stand out in the perception of the riverside people: natural and cultural elements of the landscape. In the natural elements, the dynamics of the waters and the heat, among the cultural ones, the ladders and the Church. Of all the elements mentioned, the heat is the most prominent, both in the groups of men and women in all the communities worked on. The maps and the narratives point out subtle differences in the perceptions between the groups, the same ones, having greater negative impacts in the extreme droughts. Community members perceive changes in relation to river and rain events, and temperature increase through heat.